Draft Genome Sequences of Ralstonia solanacearum Race 3 Biovar 2 Strains with Different Temperature Adaptations - Yuan, Kat (Xiaoli) (Genome Announc, 2015)
Ralstonia solanacearum race 3 biovar 2 (R3bv2) causes brown rot of potato in countries with temperate climates. Here, we report two draft genome sequences of R. solanacearum R3bv2 NCPPB909 and CFIA906 with different temperature adaptations. Analysis of these genome sequences will provide detailed insight on virulence, functionality, and plant/pest interactions of this widely distributed and regulated pathogen.